Muslimah Event sebagai Upaya Membangun Karakter Muslimah dengan Al-Qur’an dan Bahasa Arab di Era Millenium - Rosmita Rosmita; Munawara Munawara; Nasaruddin Nasaruddin (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2023)
Muslimah Event is one of the routine activities which is carried out once a year by STIBA Makassar students. The activity with the theme Building Muslimah Character with the Qur'an and Arabic in the Millennium Era aims to restore people's love for the Qur'an and Arabic. This activity was enriched by a series of various competitions. This event took place at the Grand Diamond Ballroom by Myko Makassar because it is a strategic place and is in great demand by Muslim women in particular. This activity was carried out in collaboration with three SMEs; 1) Da'wah Department of the Women's Student Executive Council (DEMA); 2) Memorization Division of UKM Raudhatul Huffaazh Putri; and 3) the Language Development Division of UKM al-Fusha which synergizes with each other to spread the da'wah of the Qur'an and Arabic, especially in the city of Makassar. The results of its activities were successful in bringing as many as 1221 Muslim women. As a follow-up to the activity, 81 people formed Halaqah Tahsin and Arabic Language which were divided into 10 groups